A pilot study of hyperoxemia on neurological injury, inflammation and oxidative stress. Issue 6 (20th February 2018) - Lång, M.; Skrifvars, M. B.; Siironen, J.; Tanskanen, P.; Ala‐Peijari, M.; Koivisto, T.; Djafarzadeh, S.; Bendel, S.
Abstract : Background: Normobaric hyperoxia is used to alleviate secondary brain ischaemia in patients with traumatic brain injury (TBI), but clinical evidence is limited and hyperoxia may cause adverse events. Methods: An open label, randomised controlled pilot study comparing blood concentrations of reactive oxygen species (ROS), interleukin 6 (IL‐6) and neuron‐specific enolase (NSE) between two different fractions of inspired oxygen in severe TBI patients on mechanical ventilation. Results: We enrolled 27 patients in the Fi O2 0.40 group and 38 in the Fi O2 0.70 group; 19 and 23 patients, respectively, completed biochemical analyses. In baseline, there were no differences between Fi O2 0.40 and Fi O2 0.70 groups, respectively, in ROS (64.8 nM [22.6–102.1] vs. 64.9 nM [26.8–96.3], P = 0.80), IL‐6 (group 92.4 pg/ml [52.9–171.6] vs. 94.3 pg/ml [54.8–133.1], P = 0.52) or NSE (21.04 ug/l [14.0–30.7] vs. 17.8 ug/l [14.1–23.9], P = 0.35). ROS levels did not differ at Day 1 (24.2 nM [20.6–33.5] vs. 29.2 nM [22.7–69.2], P = 0.10) or at Day 2 (25.4 nM [21.7–37.4] vs. 47.3 nM [34.4–126.1], P = 0.95). IL‐6 concentrations did not differ at Day 1 (112.7 pg/ml [65.9–168.9) vs. 83.9 pg/ml [51.8–144.3], P = 0.41) or at Day 3 (55.0 pg/ml [34.2–115.6] vs. 49.3 pg/ml [34.4–126.1], P = 0.95). NSE levels did not differ at Day 1 (15.9 ug/l [9.0–24.3] vs. 15.3 ug/l [12.2–26.3], P = 0.62). There were no differences between groups in the incidence of pulmonary complications. Conclusion: Higher fraction of inspired oxygen did not increase blood concentrations of markers of oxidative stress, inflammation or neurological injury or the incidence of pulmonary complications in severe TBI patients on mechanical ventilation.